National Audiovisual Preservation Initiatives and the Independent Media Arts in Canada - Wozny, Michele L. (Archivaria, 2009)
As an introduction to historical preservation initiatives on behalf of audiovisual documents that have affected contemporary policy and practices at the federal level in Canada, this paper documents the efforts of archival activists who have built a framework that has helped safeguard only a very small percentage of Canadian, independent media artwork. It is important that contemporary activists, be they archivists, artists, or policy administrators, understand the key issues that have created the preservation crisis that currently threatens the future of Canada’s independent media artwork in our collective history. RÉSUMÉ Afin de servir d’introduction aux initiatives historiques de conservation de documents audiovisuels qui ont eu un impact sur les politiques et pratiques contemporaines au niveau fédéral canadien, ce texte trace les efforts des militants archivistes qui ont conçu un cadre de travail ayant permis de ne sauvegarder qu’un petit pourcentage des oeuvres d’art médiatiques indépendantes au Canada. Il est important de comprendre les principales questions à l’origine de la crise de la conservation qui menace l’avenir même des oeuvres d’art médiatiques dans notre histoire collective canadienne.